PRELIMINARY DATA OF THE SCREENING OF NEUROPSYCHOLOGICAL ALTERATIONS IN MOTRICITY AREA (Fiep Bulletin - online, 2011)
INTRODUCTION: An increasing attention from health professionals for the elderly. Given the importance of neuropsychological and their relationship to psychomotor factors in senescence, we performed a study on the subject. OBJECTIVES: To investigate symptoms related to changes in manual aptitude, spatial and temporal orientation in healthy elderly and to obtain preliminary data concerning the neuropsychological through Neuropsychological Alterations Inventory - SZC (2009). METHODS: For research purposes, we used the Inventory of Neuropsychological Alterations for Adults - SZC (developed by Schlindwein-Zanini and Cruz, 2009) in 10 individuals aged between 60 and 70 years from the state of Santa Catarina - Brazil that did not received a diagnosis of psychological disorders, neurological and/or neuropsychological previously, who agreed to participate. In the discussion and description of the results it was selected for more details in this article, the issues of SZC related to spatial orientation, temporal orientation and manual aptitude. RESULTS AND CONCLUSIONS: The majority of the sample individuals showed no signs of changes related to spatial orientation and temporal orientation, but most showed signs of changes in manual aptitude, 40% being "soft" and 20% "moderate", suggesting the need for specific motor and neuropsychological interventions; Inventory neuropsychological alterations SZC was a good screening instrument for neuropsychological disturbances, including the elderly, the SZC proved to be a good tool to screen for symptoms related to disorders of manual aptiude , temporal orientation and space orientation, which can relate to neuropsychological disorders such as Alzheimer and Parkinson diseases, for example, the individuals of the sample showed a good understanding of the instrument, indicating that it can be applied in different samples.
Keywords: neuropsychological alterations; motor alterations; the elderly